Immunofluorescence-assisted investigation of Human Astrovirus-1 in oyster processing and production - Hyewon Song; Sangha Han; Hyobin Lee; Ye In Moon; Si-Hong Park; Sang-Do Ha (Food Microbiology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Energy-efficient direct air capture combining an impeller-based scrubber and anion exchange membrane electrolysis - Sunghyeon Han; Jongmin Jin; Hui Song; Jong-In Han (Chemical Engineering Journal, 2025)

High-purity Li₆PS₅Cl sulfide solid electrolytes via liquid-phase method synthesis for high-performance all-solid-state Li-ion batteries: Particle-scale analysis of formation with precursor and solvent optimization - Hyewon Jo; Bitna Kim; Byeong-Min Ahn; Youngjun Huh; Soyoung Kim; Jung Han Kim; Heetaek Park; Jun-Woo Park; Yoon-Cheol Ha; Jay Hyok Song; Je In Lee; Jun-Ho Park (Chemical Engineering Journal, 2025)

Multi-Enzyme Supplementation to Diets Containing 2 Protein Levels Affects Intramuscular Fat Content in Muscle and Modulates Cecal Microflora Without Affecting the Growth Performance of Finishing Pigs - Qianqian Zhang; Sungbo Cho; Junho Song; Jinuk Jeong; Minjae Yu; Seyoung Mun; Kyudong Han; In Ho Kim (Probiotics and Antimicrobial Proteins, 2025)

Correction to: PRDX6 Inhibits Neurogenesis through Downregulation of WDFY1-Mediated TLR4 Signal - In Jun Yeo; Mi Hee Park; Dong Ju Son; Ji Young Kim; Kyoung Tak Nam; Byung Kook Hyun; So Young Kim; Myung Hee Jung; Min Ji Song; Hyung Ok Chun; Tae Hyung Lee; Sang-Bae Han; et al. (Molecular Neurobiology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Transparent and visible light-activated antimicrobial air filters from electrospun crystal violet-embedded polyacrylonitrile nanofibers - Seung Yeon Lee; Jae Hak Shin; In Ho Kim; Dong Yun Choi; Dong Uk Lee; Gi Byoung Hwang; Bangwoo Han; Sang Bok Kim; Dong-Keun Song; Inyong Park; Jae Hee Jung (Environmental Research, 2025)

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

Evolution-aided improvement of the acid tolerance of Levilactobacillus brevis and its application in sourdough fermentation - Na Ree Han; Sora Yu; Jung A Byun; Eun Ju Yun; Seongwon Cheon; Seongbong Song; Sangmin Shim; In-Geol Choi; Sung-Ho Lee; Kyoung Heon Kim (Food Research International, 2024)

Consumer-driven characterization of healing foods using Q methodology and Q based sorting - Ki-Beom Song; Sébastien Lê; Haeng-Ran Kim; Seon-Mi Yoo; Min-Sook Kang; Han-Na Chu; In-Seon Hwang; Jae-Hee Hong (Food Quality and Preference, 2024)

Maternal PM2.5 exposure is associated with preterm birth and gestational diabetes mellitus, and mitochondrial OXPHOS dysfunction in cord blood - Young-Ah You; Sunwha Park; Eunjin Kwon; Ye-Ah Kim; Young Min Hur; Ga In Lee; Soo Min Kim; Jeong Min Song; Man S. Kim; Young Ju Kim; Young-Han Kim; Sung Hun Na; et al. (Environmental Science and Pollution Research, 2024)
Maternal exposure to fine particulate matter (PM 2.5 ) is associated with adverse pregnancy and neonatal health outcomes. To explore the mechanism, we performed mRNA sequencing of neonatal cord blood. From an ongoing prospective cohort, Air Pollution on Pregnancy Outcome (APPO) study, 454 pregnant women from six centers between January 2021 and June 2022 were recruited. Individual PM 2.5 exposure was calculated using a time-weighted average model. In the APPO study, age-matched cord blood samples from the High PM 2.5 (˃15 ug/m 3 ; n = 10) and Low PM 2.5 (≤ 15 ug/m 3 ; n = 30) groups were randomly selected for mRNA sequencing. After selecting genes with differential expression in the two groups ( p -value < 0.05 and log2 fold change > 1.5), pathway enrichment analysis was performed, and the mitochondrial pathway was analyzed using MitoCarta3.0. The risk of preterm birth (PTB) increased with every 5 µg/m 3 increase of PM 2.5 in the second trimester (odds ratio 1.391, p = 0.019) after adjusting for confounding variables. The risk of gestational diabetes mellitus (GDM) increased in the second (odds ratio 1.238, p = 0.041) and third trimester (odds ratio 1.290, p = 0.029), and entire pregnancy (odds ratio 1.295, p = 0.029). The mRNA-sequencing of cord blood showed that genes related to mitochondrial activity (FAM210B, KRT1, FOXO4, TRIM58, and FBXO7) and PTB-related genes (ADIPOR1, YBX1, OPTN, NFkB1, HBG2) were upregulated in the High PM 2.5 group. In addition, exposure to high PM 2.5 affected mitochondrial oxidative phosphorylation (OXPHOS) and proteins in the electron transport chain, a subunit of OXPHOS. These results suggest that exposure to high PM 2.5 during pregnancy may increase the risk of PTB and GDM, and dysregulate PTB-related genes. Alterations in mitochondrial OXPHOS by high PM 2.5 exposure may occur not only in preterm infants but also in normal newborns. Further studies with larger sample sizes are required.

Efficient MAPbI3-based perovskite solar cells exceeding 21% efficiency via aging treatment - Dae Woo Kim; Young Wook Noh; Jongmin Han; Hye Seung Kim; Chung Hyeon Jang; Ji A. Hong; Sangmi Park; Min Hyeong Lee; Ye In Kim; Myoung Hoon Song (Chemical Engineering Journal, 2023)

Protective effects of esomeprazole against cisplatin-induced ototoxicity: an in vitro and in vivo study - Hanul Jeon; In Sik Song; Jin-Gyeong Park; Hyejin Lee; Eunjung Han; Saemi Park; Yunkyoung Lee; Chi-man Song; Wooyoung Hur; In-Gyun Lee; June Choi (Aquatic Toxicology, 2023)

A rice seed-specific glycine-rich protein OsDOR1 interacts with GID1 to repress GA signaling and regulates seed dormancy - Sooyeon Kim; Sun Mi Huh; Hay Ju Han; Gang Seob Lee; Yong-Sic Hwang; Mi Hyun Cho; Beom-Gi Kim; Ji Sun Song; Joo Hee Chung; Myung Hee Nam; Hyeonso Ji; Kyung-Hwan Kim; et al. (Plant Molecular Biology, 2023)

Sargassum horneri and Ascophyllum nodosum extracts enhance thermal tolerance and antioxidant activity of Neopyropia yezoensis - Sol Han; Hye-In Song; Ji-Sook Park; Youn-Jung Kim; Schery Umanzor; Charles Yarish; Jang K. Kim (Journal of Applied Phycology, 2023)

Antiviral activity of canine interferon lambda 3 expressed using a recombinant adenovirus against canine coronavirus, canine parvovirus, and canine distemper virus - Dong-Hwi Kim; Sang-Hoon Han; Hyeon-Jeong Go; Da-Yoon Kim; Jae-Hyeong Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Veterinary Research Communications, 2022)

T cell receptor repertoires of ex vivo–expanded tumor-infiltrating lymphocytes from breast cancer patients - In Ah Park; Hajar Rajaei; Young-Ae Kim; Hyeonjin Lee; Heejae Lee; Jeong-Han Seo; Sun-Hee Heo; In Hye Song; Gyungyub Gong; Hee Jin Lee (Immunologic Research, 2020)

Relationship between neuropilin-1 expression and prognosis, according to gastric cancer histology - Ho Seok Seo; Jiyeon Hyeon; In Hye Song; Han Hong Lee (Journal of Molecular Histology, 2020)

A comparative evaluation of BACT/ALERT FA PLUS and FN PLUS blood culture bottles and BD BACTEC Plus Aerobic and Anaerobic blood culture bottles for antimicrobial neutralization - Yousun Chung; In-Hee Kim; Minje Han; Hyun Soo Kim; Han-Sung Kim; Wonkeun Song; Jae-Seok Kim (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Exploring the Probiotic and Compound Feed Fermentative Applications of Lactobacillus plantarum SK1305 Isolated from Korean Green Chili Pickled Pepper - Kai-Min Niu; Damini Kothari; Sang-Buem Cho; Sung-Gu Han; In-Geun Song; Sam-Churl Kim; Soo-Ki Kim (Probiotics and Antimicrobial Proteins, 2019)

PRDX6 Inhibits Neurogenesis through Downregulation of WDFY1-Mediated TLR4 Signal - In Jun Yeo; Mi Hee Park; Dong Ju Son; Ji Young Kim; Kyoung Tak Nam; Byung Kook Hyun; So Young Kim; Myung Hee Jung; Min Ji Song; Hyung Ok Chun; Tae Hyung Lee; Sang-Bae Han; et al. (Molecular Neurobiology, 2019)
Impaired neurogenesis has been associated with several brain disorders, such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). The role of peroxiredoxin 6 (PRDX6) in neurodegenerative diseases is very controversial. To demonstrate the role of PRDX6 in neurogenesis, we compared the neurogenesis ability of PRDX6-overexpressing transgenic (Tg) mice and wild-type mice and studied the involved molecular mechanisms. We showed that the neurogenesis of neural stem cells (NSCs) and the expression of the marker protein were lower in PRDX6 Tg-mice than in wild-type mice. To determine the factors involved in PRDX6-related neural stem cell impairment, we performed a microarray experiment. We showed that the expression of WDFY1 was dramatically decreased in PRDX6-Tg mice. Moreover, WDFY1 siRNA decreases the differentiation ability of primary neural stem cells. Interestingly, WDFY1 reportedly recruits the signaling adaptor TIR-domain-containing adapter-inducing interferon-β (TRIF) to toll-like receptors (TLRs); thus, we showed the relationship among TLRs, PRDX6, and WDFY1. We showed that TLR4 was dramatically reduced in PRDX6 Tg mice, and reduced TLR4 expression and neurogenesis was reversed by the introduction of WDFY1 plasmid in the neural stem cells from PRDX6 Tg mice. This study indicated that PRDX6 inhibits the neurogenesis of neural precursor cells through TLR4-dependent downregulation of WDFY1 and suggested that the inhibitory effect of PRDX6 on neurogenesis play a role in the development of neurodegenerative diseases in the PRDX6 overexpressing transgenic mice.

Evidence of hepatitis E virus infection in specific pathogen-free rabbits in Korea - Sang-Hoon Han; Byung-Joo Park; Hee-Seop Ahn; Yong-Hyun Kim; Hyeon-Jeong Go; Dong-Hwi Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Virus Genes, 2018)

Allelic variation in Brassica oleracea CIRCADIAN CLOCK ASSOCIATED 1 (BoCCA1) is associated with freezing tolerance - Hayoung Song; Hankuil Yi; Ching-Tack Han; Jong-In Park; Yoonkang Hur (Horticulture, Environment, and Biotechnology, 2018)

Development of an Observation Processing Package for Data Assimilation in KIAPS - Jeon-Ho Kang; Hyoung-Wook Chun; Sihye Lee; Ji-Hyun Ha; Hyo-Jong Song; In-Hyuk Kwon; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Tae-Hun Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Development of an Operational Hybrid Data Assimilation System at KIAPS - In-Hyuk Kwon; Hyo-Jong Song; Ji-Hyun Ha; Hyoung-Wook Chun; Jeon-Ho Kang; Sihye Lee; Sujeong Lim; Youngsoon Jo; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Seoleun Shin; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Effects of 7-MEGA TM 500 on Oxidative Stress, Inflammation, and Skin Regeneration in H 2 O 2 -Treated Skin Cells - In-Bong Song; Hyejung Gu; Hye-Ju Han; Na-Young Lee; Ji-Yun Cha; Yeon-Kyong Son; Jungkee Kwon (Toxicological Research, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Transgenic Turfgrasses Expressing Hyperactive Ser599Ala Phytochrome A Mutant Exhibit Abiotic Stress Tolerance - Mayank Anand Gururani; Markkandan Ganesan; In-Ja Song; Yunjeong Han; Jeong-Il Kim; Hyo-Yeon Lee; Pill-Soon Song (Journal of Plant Growth Regulation, 2016)

Inhibitory effect of snake venom toxin on NF-κB activity prevents human cervical cancer cell growth via increase of death receptor 3 and 5 expression - Hye Lim Lee; Mi Hee Park; Ji Eun Hong; Dae Hwan Kim; Ji Young Kim; Hyen Ok Seo; Sang-Bae Han; Joo Hee Yoon; Won Hyoung Lee; Ho Sueb Song; Ji In Lee; Ung Soo Lee; et al. (Archives of Toxicology, 2016)

Echinochrome A regulates phosphorylation of phospholamban Ser16 and Thr17 suppressing cardiac SERCA2A Ca2+ reuptake - Hyoung Kyu Kim; Jae Boum Youm; Seung Hun Jeong; Sung Ryul Lee; In-Sung Song; Tae Hee Ko; Julius Ryan Pronto; Kyung Soo Ko; Byoung Doo Rhee; Nari Kim; Bernd Nilius; Natalia P. Mischchenko; et al. (Pflügers Archiv - European Journal of Physiology, 2015)

Glycan structure and serum half-life of recombinant CTLA4Ig, an immunosuppressive agent, expressed in suspension-cultured rice cells with coexpression of human β1,4-galactosyltransferase and human CTLA4Ig - Seung Hoon Kang; Hahn Sun Jung; Song Jae Lee; Cheon Ik Park; Sang Min Lim; Heajin Park; Byung Sun Kim; Kwang Heum Na; Gyeong Jin Han; Jae Woo Bae; Hyun Joo Park; Keuk Chan Bang; et al. (Glycoconjugate Journal, 2015)

B7-H4 downregulation induces mitochondrial dysfunction and enhances doxorubicin sensitivity via the cAMP/CREB/PGC1-α signaling pathway in HeLa cells - Hyoung Kyu Kim; In-Sung Song; Sun Young Lee; Seung Hun Jeong; Sung Ryul Lee; Hye Jin Heo; Vu Thi Thu; Nari Kim; Kyung Soo Ko; Byoung Doo Rhee; Dae Hun Jeong; Young Nam Kim; et al. (Pflügers Archiv - European Journal of Physiology, 2014)

Dioscin induces caspase-independent apoptosis through activation of apoptosis-inducing factor in breast cancer cells - Eun-Ae Kim; Ji-Hoon Jang; Yun-Han Lee; Eon-Gi Sung; In-Hwan Song; Joo-Young Kim; Suji Kim; Ho-Yong Sohn; Tae-Jin Lee (Apoptosis, 2014)

Comparative analysis of physicochemicals and antioxidative properties in new red rice (Oryza sativa L. cv. Gunganghongmi) - Woo Duck Seo; Jun Young Kim; You-Chun Song; Jun-Hyun Cho; Ki Chang Jang; Sang-Ik Han; Ji-Eun Ra; Seong-Hwan Oh; Hyeon-Jung Kang; Byung-Joo Kim; Nam-In Baek; Rak-Hun Jeong; et al. (Journal of Crop Science and Biotechnology, 2013)

Non-genomic effect of glucocorticoids on cardiovascular system - Sung Ryul Lee; Hyoung Kyu Kim; Jae Boum Youm; Louise Anne Dizon; In Sung Song; Seung Hun Jeong; Dae Yun Seo; Kyoung Soo Ko; Byoung Doo Rhee; Nari Kim; Jin Han (Pflügers Archiv - European Journal of Physiology, 2012)

Erratum to: Overexpression of phytochrome A and its hyperactive mutant improves shade tolerance and turf quality in creeping bentgrass and zoysiagrass - Markkandan Ganesan; Yun-Jeong Han; Tae-Woong Bae; Ok-Jin Hwang; Thummala Chandrasekhar; Ah-Young Shin; Chang-Hyo Goh; Satoshi Nishiguchi; In-Ja Song; Hyo-Yeon Lee; Jeong-Il Kim; Pill-Soon Song (Planta, 2012)

Overexpression of phytochrome A and its hyperactive mutant improves shade tolerance and turf quality in creeping bentgrass and zoysiagrass - Markkandan Ganesan; Yun-Jeong Han; Tae-Woong Bae; Ok-Jin Hwang; Thummala Chandrasekkhar; Ah-Young Shin; Chang-Hyo Goh; Satoshi Nishiguchi; In-Ja Song; Hyo-Yeon Lee; Jeong-Il Kim; Pill-Soon Song (Planta, 2012)

Gene expression analysis identifies DNA damage-related markers of benzo[a]pyrene exposure in HepG2 human hepatocytes - Mi-Kyung Song; Ji-Seong Yoon; Mee Song; Han-Seam Choi; Chan-Young Shin; Youn-Jung Kim; Woo-In Ryu; Hyo-Sun Lee; Jae-Chun Ryu (Toxicology and Environmental Health Sciences, 2012)

A genome-wide association analysis reveals 1p31 and 2p13.3 as susceptibility loci for Kawasaki disease - Jae-Jung Kim; Young Mi Hong; Saejung Sohn; Gi Young Jang; Kee-Soo Ha; Sin Weon Yun; Myung Ki Han; Kyung-Yil Lee; Min Seob Song; Hyoung Doo Lee; Dong Soo Kim; Jong-Eun Lee; et al. (Human Genetics, 2011)

Extract of Poncirus trifoliata fruit reduces elevated serum IgE concentrations in chemically induced allergic model mice - Hyun Jung Park; Jong Bo Kim; In Song Han; Jin Hoi Kim; Bokyung Kim; Sung-Ho Kang; Ho-Sung Jung; Sang Ho Moon; Si Heung Sung; Hyuk Song (Horticulture, Environment, and Biotechnology, 2011)

Hesperidin inhibits expression of hypoxia inducible factor-1 alpha and inflammatory cytokine production from mast cells - In-Young Choi; Su-Jin Kim; Hyun-Ja Jeong; Seong-Heak Park; Yong-Sun Song; Ji-Hyun Lee; Tae-Hee Kang; Jin-Han Park; Gab-Soo Hwang; Eon-Jeong Lee; Seung-Heon Hong; Hyung-Min Kim; et al. (Molecular and Cellular Biochemistry, 2007)

Vegetation of Barton Peninsula in the neighbourhood of King Sejong Station (King George Island, maritime Antarctic) - Ji Hee Kim; In-Young Ahn; Kyu Song Lee; Hosung Chung; Han-Gu Choi (Polar Biology, 2007)

Influence of reducing agents on the secretion rate of recombinant erythropoietin from CHO cells - Sung Kwan Yoon; Yong-Ho Ahn; In-Chan Kwon; Kyuboem Han; Ji Yong Song (Biotechnology Letters, 1998)